(untitled) (LEARNing Landscapes, 2014)
Through the storied experiences of a Highly Sensitive Child (HSC), the author creates a picture of what High Sensitivity is and how it impacts children in the classroom. Discussion focuses on attending to the needs of highly sensitive children, specifically addressing friendship, environment, discipline, stimulation, and reciprocal learning relationships. The author makes visible why it is important to create a classroom life that meets the needs of highly sensitive children and theorizes that, in doing so, the bar for attending to the wellness of all children will be raised. This article begins a conversation about highly sensitive children in the classroom, something not currently being addressed in educational literature.